THE IMPACT OF GARHWAL'S RAMLILA ON SOCIETY: A MUSICAL STUDY: गढ़वाल की रामलीला का समाज पर प्रभावः एक सांगीतिक अध्ययन - Kumar Pathak, Santosh; Chitkariya, Nidhi (International Journal of Research -GRANTHAALAYAH, 2015)
Indian culture includes various cultural streams in itself, in these cultural streams one stream Maryada Purushottam Lord Rama's Leela is also included. Its own distinct flow is clearly visible, which is present in the literature of Indian culture and in its cultural and cultural influence in society. The specialty of Shri Rama's character is that he awakened the new world to new consciousness-power by giving a message to the entire world on the path of the journey of human life, like a common traveler, and the whole world made him docile. Ramlila Manchan is a lake of this kind of life, in which all kinds of vices like one nationality, caste discrimination, apartheid distinction, difference of poor and rich, lose their existence and become one in which high qualities of human qualities are reflected. . With these ideals, Ramlila of Garhwal has been associated with the society here for more than 100 years. Even today, the people settling in the society here staging 'Musical Ramlila' with great enthusiasm. Which is the main feature of Garhwal's Ramlila. भारतीय संस्कृति अपने में विभिन्न सांस्कृतिक धाराओं को समेटे हुये है, इन्हीं सांस्कृतिक धाराओं में एक धारा मर्यादा पुरूषोत्तम भगवान राम की लीला भी समाहित है। इसका अपना एक अलग प्रवाह स्पष्ट रूप से दृष्टिगोचर होता है, जो भारतीय संस्कृति के साहित्य में तथा समाज में अपनी सांस्कृतिक व संस्कारित प्रभाव में विद्यमान है। श्री राम के चरित्र का वैषिष्ट्य यही है कि उन्होंने मानव जीवन की यात्रा के मार्ग पर सम्पूर्ण विष्व को समान पथ-यात्री का संदेष देकर नई चेतना-शक्ति को जाग्रत किया और समस्त विष्व ने उन्हे वंदनीय बना दिया। रामलीला मंचन इसी प्रकार के जीवन दर्षन का सरोवर है, जिसमें एक देषीयता, जाति भेद, वर्णभेद ऊँच-नीच का भेद, गरीब अमीर का भेद जैसे सभी प्रकार के विकार अपना अस्तित्व खोकर एक हो जाते हैं तथा जिसमें मानवीय गुणों का उच्चादर्ष परिलक्षित होता हैं। इन्हीं आदर्षों के साथ गढ़वाल की रामलीला 100 वर्षों से भी अधिक समय से यहाँ के समाज से जुड़ी है। आज भी यहाँ के समाज में बसने वाले लोग बड़े ही चाव के साथ ‘संगीतमय रामलीला का मंचन करते है। जो कि गढ़वाल की रामलीला की मुख्य विषेषता है।